PENGEMBANGAN BAHAN AJAR GAMBAR BERSERI BERBASIS MENULIS IMAJINATIF PADA KETERAMPILAN MENULIS CERITA MUATAN BAHASA INDONESIA KELAS III SD NO.1 KEROBOKAN - Septarianti, Anak Agung Dwi Purba; Wulandari, I Gusti Agung Ayu; Ganing, Ni Nyoman (Jurnal Pendidikan Dasar, 2021)
The use of picture series teaching materials based on imaginative writing on story writing skills in grade III SD No.1 Kerobokan. Online learning requires a learning media in writing skills that can increase students' enthusiasm for learning. In this study, a development model is applied, namely, the ADDIE model in the development stage. In this study, the method used in collecting data is in the form of a questionnaire or questionnaire which is equipped with interviews and observations. Development research using data analysis techniques is quantitative and qualitative descriptive analysis. This study uses individual test subjects as many as 3 students of class III with different levels of learning outcomes while the subject of small group trials as many as 9 students of class III. The results of the assessment from the expert expert test stage are, the assessment of the subject content expert test with a percentage of 95% in the very good category, then by the learning design expert with a percentage of 90% in the very good category, and by the learning media expert test with a percentage of 89.58% in the good category. For individual trials, a percentage of 85.71% is categorized as good and small group trials get a percentage of 92.39% in the very good category.